Metal foil resin sheet
Patent Information
- Application Number
- JP2022164870
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-10-13
AI Technical Summary
【0010】 本発明によれば、ロール形成性に優れる金属箔付き樹脂シート;当該金属箔付き樹脂シートをロール状に巻き取ったロール状金属箔付き樹脂シート;当該金属箔付き樹脂シートを用いて製造される回路基板及び当該回路基板を備える半導体装置を提供することができる。
Smart Images

Figure 0007652169000001 
Figure 0007652169000002 
Figure 0007652169000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin sheet with a metal foil, and further to a circuit board manufactured by using the resin sheet with a metal foil and a semiconductor device including the circuit board. [Background technology]
[0002] Circuit boards such as printed wiring boards, which are widely used in various electronic devices, are required to have thinner layers and finer wiring in order to miniaturize and improve the functionality of electronic devices. A known manufacturing technique for circuit boards is a manufacturing method using a build-up method in which insulating layers and conductor layers (wiring layers) are alternately stacked. In a manufacturing method using the build-up method, an insulating layer is generally formed by thermally curing a resin composition layer in a resin sheet, and a conductor layer is formed by a technique such as a semi-additive process (SAP), a modified semi-additive process (MSAP), or a subtractive process.
[0003] In recent years, a method has been proposed for forming a conductor layer on an insulating layer by using a resin sheet with a metal foil and using the metal foil as the conductor layer (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-43685 [Patent Document 2] JP 2010-161497 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although the resin sheet with metal foil is used as a single sheet, in order to efficiently form the insulating layer and the conductor layer, a method can be considered in which the resin sheet with metal foil is wound into a roll and the insulating layer and the conductor layer are continuously formed using the rolled resin sheet with metal foil.
[0006] However, when a resin sheet with a metal foil is rolled, the resin sheet with the metal foil may bend, crack or chip due to the stress applied when rolling, that is, the roll formability may be poor.
[0007] The present invention has been devised in consideration of the above-mentioned problems, and aims to provide: a resin sheet with a metal foil that has excellent roll formability; a roll-shaped resin sheet with a metal foil obtained by winding the resin sheet with a metal foil into a roll; a circuit board manufactured using the resin sheet with a metal foil; and a semiconductor device including the circuit board. [Means for solving the problem]
[0008] As a result of extensive research, the inventors have discovered that a resin sheet with metal foil, which is composed of a metal foil, a resin composition layer, and a protective film laminated in that order, can be formed by adjusting the thickness of each layer and the elastic modulus of each layer before the resin composition layer is hardened so as to satisfy a predetermined relationship, thereby making it possible to prevent the resin sheet with metal foil from bending, cracking, or chipping even when the sheet is rolled up. This has led to the completion of the present invention.
[0009] That is, the present invention includes the following. [1] A resin sheet with a metal foil, comprising a metal foil, a resin composition layer, and a protective film laminated in this order, The thickness of the metal foil is a (μm), and the elastic modulus of the metal foil at 23°C is A (GPa). The thickness of the resin composition layer is b (μm), and the elastic modulus of the resin composition layer at 23° C. is B (GPa), A resin sheet with a metal foil, which satisfies both of the following formulas (1) and (2), when the thickness of the protective film is c (μm) and the elastic modulus of the protective film at 23° C. is C (GPa). 0.2≦(c×C) / (b×B)≦8 (1) 3≦(a×A) / (b×B)≦30 (2) [2] The resin sheet with a metal foil according to [1], wherein the resin composition layer contains (A) an inorganic filler. [3] The resin sheet with a metal foil according to [2], wherein the content of the component (A) is 55% by mass or more and 85% by mass or less, when the total amount of non-volatile components in the resin composition layer is 100% by mass. [4] The resin sheet with a metal foil according to any one of [1] to [3], wherein the resin composition layer contains an epoxy resin (B). [5] The resin sheet with a metal foil according to any one of [1] to [4], wherein the resin composition layer contains a liquid resin. [6] The resin sheet with a metal foil according to [5], wherein the content of the liquid resin is 5% by mass or more and 25% by mass or less, when the non-volatile components in the resin composition layer are taken as 100% by mass. [7] The resin sheet with a metal foil according to any one of [1] to [6], wherein a / b is 0.1 or more and 2 or less, where a (μm) is the thickness of the metal foil and b (μm) is the thickness of the resin composition layer. [8] The resin sheet with a metal foil according to any one of [1] to [7], wherein, when the thickness of the resin composition layer is b (μm) and the thickness of the protective film is c (μm), c / b is 0.3 or more and 4 or less. [9] The resin sheet with a metal foil according to any one of [1] to [8], wherein the metal foil is a copper foil.
[10] A roll-shaped resin sheet with a metal foil, which is obtained by winding up the resin sheet with a metal foil according to any one of [1] to [9] into a roll.
[11] The roll-shaped resin sheet with a metal foil according to
[10] , having a roll diameter of 6 cm or more.
[12] A circuit board comprising an insulating layer formed from a cured product of a resin composition layer of a resin sheet with a metal foil according to any one of [1] to [9], and a conductor layer formed from the metal foil of the resin sheet with a metal foil according to any one of [1] to [9].
[13] A semiconductor device comprising the circuit board according to
[12] . Effect of the Invention
[0010] According to the present invention, it is possible to provide a resin sheet with a metal foil that has excellent roll formability; a roll-shaped resin sheet with a metal foil obtained by winding the resin sheet with a metal foil into a roll; a circuit board manufactured using the resin sheet with a metal foil, and a semiconductor device including the circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below with reference to the following embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0012] [Resin sheet with metal foil] The resin sheet with metal foil of the present invention is formed by laminating a metal foil, a resin composition layer, and a protective film in this order, and satisfies all of the following formulas (1) and (2) when the thickness of the metal foil is a (μm), the elastic modulus of the metal foil at 23° C. is A (GPa), the thickness of the resin composition layer is b (μm), the elastic modulus of the resin composition layer at 23° C. is B (GPa), the thickness of the protective film is c (μm), and the elastic modulus of the protective film at 23° C. is C (GPa). By using such a resin sheet with metal foil, it is possible to provide a resin sheet with metal foil that is excellent in roll formability. The elastic modulus B of the resin composition layer at 23° C. is the elastic modulus before the resin composition layer is cured. 0.2≦ (c×C) / (b×B) ≦8···(1) 3≦ (a×A) / (b×B) ≦30 (2)
[0013] The parameter expressed by Eq. (1) (c×C) / (b×B) " is in the range of 0.2 or more, preferably 0.5 or more, more preferably 0.8 or more, and even more preferably 1 or more. The upper limit is 8 or less, preferably 7 or less, more preferably 6 or less, and even more preferably 5 or less, 3 or less, or 2 or less.
[0014] The parameter expressed by equation (2) (a×A) / (b×B) " is in the range of 3 or more, preferably 4 or more, more preferably 5 or more, and even more preferably 5.5 or more. The upper limit is 30 or less, preferably 28 or less, more preferably 20 or less, and even more preferably 10 or less, 8 or less, or 7 or less.
[0015] Parameter " (c×C) / (b×B) " and " (a×A) / (b×B) In the case where " is within such a range, the roll formability is excellent. Furthermore, the resin sheet with the metal foil usually has a high breaking strength and glass transition temperature (Tg), a low coefficient of linear thermal expansion (CTE), and can give a cured product with excellent lamination properties and peelability.
[0016] In general, when the elastic modulus of a resin composition layer before curing is high, the resin composition layer tends to be brittle. Therefore, when a resin sheet with a metal foil is rolled, it is easily affected by stress, and the roll formability tends to be poor. In addition, when the elastic modulus of a resin composition layer before curing is low, the linear thermal expansion coefficient tends to be too high and the insulation reliability tends to be poor. In addition, when the elastic modulus of a resin composition layer before curing is low, the adhesion with a protective film tends to be high, and the peelability of the protective film tends to be poor. In contrast, (c×C) / (b×B) " and " (a×A) / (b×B) When " is in such a range, the above-mentioned problems are suppressed and a resin sheet with a metal foil having excellent roll formability can be provided.
[0017] From the viewpoint of obtaining the effect of the present invention remarkably, the elastic modulus A of the metal foil is preferably 30 GPa or more, more preferably 50 GPa or more, and even more preferably 60 GPa or more, and is preferably 150 GPa or less, more preferably 120 GPa or less, and even more preferably 100 GPa or less. The elastic modulus of the metal foil is the elastic modulus in the MD direction of the rolled resin sheet with the metal foil, and this elastic modulus can be measured by the method described in the examples below. The MD direction corresponds to the longitudinal direction of the rolled resin sheet with the metal foil. When the metal foil has a multi-layer structure, the total elastic modulus of each layer is preferably within the above range.
[0018] From the viewpoint of obtaining the effects of the present invention remarkably, the elastic modulus B of the resin composition layer before curing is preferably 1 GPa or more, more preferably 1.5 GPa or more, even more preferably 2 GPa or more, and is preferably 10 GPa or less, more preferably 8 GPa or less, even more preferably 5 GPa or less. The elastic modulus of the resin composition layer can be measured by the method described in the examples described later.
[0019] From the viewpoint of obtaining the effect of the present invention remarkably, the elastic modulus C of the protective film is preferably 1 GPa or more, more preferably 3 GPa or more, even more preferably 5 GPa or more, and is preferably 20 GPa or less, more preferably 15 GPa or less, even more preferably 10 GPa or less. The elastic modulus of the protective film is the elastic modulus in the MD direction of the rolled resin sheet with the metal foil, and this elastic modulus can be measured by the method described in the examples below. When the protective film has a multilayer structure, it is preferable that the total elastic modulus of each layer is within the above range.
[0020] From the viewpoint of obtaining the effect of the present invention remarkably, the thickness a of the metal foil is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. The thickness of the metal foil can be measured by the method described in the examples below. When the metal foil has a multi-layer structure, it is preferable that the thickness of the entire metal foil is in this range.
[0021] From the viewpoint of obtaining the effects of the present invention significantly, the thickness b of the resin composition layer is preferably 5 μm or more, more preferably 8 μm or more, even more preferably 10 μm or more, 20 μm or more, or 30 μm or more, and is preferably 60 μm or less, more preferably 55 μm or less, and even more preferably 50 μm or less. The thickness of the resin composition layer can be measured by the method described in the examples below.
[0022] From the viewpoint of obtaining the effect of the present invention remarkably, the thickness c of the protective film is preferably 3 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and is preferably 55 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less. The thickness of the protective film can be measured by the method described in the examples below. When the protective film has a release layer, it is preferable that the thickness of the entire protective film is in this range.
[0023] From the viewpoint of obtaining a remarkable effect of the present invention, the product (a×A) of the thickness a of the metal foil and the elastic modulus A of the metal foil is preferably 100 or more, more preferably 500 or more, even more preferably 1000 or more, and is preferably 2000 or less, more preferably 1500 or less, even more preferably 1200 or less.
[0024] From the viewpoint of obtaining a remarkable effect of the present invention, the product (b×B) of the thickness b of the resin composition layer and the elastic modulus B of the cured product of the resin composition layer is preferably 10 or more, more preferably 20 or more, even more preferably 30 or more, 50 or more, or 100 or more, and is preferably 350 or less, more preferably 300 or less, and even more preferably 250 or less.
[0025] From the viewpoint of obtaining a remarkable effect of the present invention, the product (c×C) of the thickness c of the protective film and the elastic modulus C of the protective film is preferably 100 or more, more preferably 150 or more, even more preferably 230 or more, and is preferably 350 or less, more preferably 300 or less, even more preferably 250 or less.
[0026] From the viewpoint of obtaining a remarkable effect of the present invention, the ratio (a / b) of the thickness a of the metal foil to the thickness b of the resin composition layer is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and is preferably 4 or less, more preferably 2 or less, even more preferably 1 or less.
[0027] From the viewpoint of obtaining a remarkable effect of the present invention, the ratio (c / b) of the thickness b of the resin composition layer to the thickness c of the protective film is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.8 or more, and is preferably 10 or less, more preferably 5 or less, even more preferably 3 or less.
[0028] <Metal foil> The resin sheet with metal foil of the present invention has a metal foil. The conductor layer of the circuit board may be formed from the metal foil.
[0029] Examples of the metal foil include copper foil and aluminum foil, and copper foil is preferred. The copper foil may be a foil made of a single metal such as copper, or may be a foil made of an alloy of copper and another metal (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0030] The metal foil may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. Examples of multi-layer metal foils include metal foils containing a carrier metal foil and an ultra-thin metal foil bonded to the carrier metal foil. Such multi-layer metal foils may include a release layer between the carrier metal foil and the ultra-thin metal foil that allows the ultra-thin metal foil to be peeled off from the carrier metal foil. The release layer is not particularly limited as long as it can peel off the ultra-thin metal foil from the carrier metal foil, and examples of the release layer include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, and the like. When a multi-layer metal foil is used, the resin composition layer is provided on the ultra-thin metal foil.
[0031] The thickness of the metal foil is as described above. When the metal foil has a multilayer structure including a carrier metal foil and an ultrathin metal foil bonded to the carrier metal foil, the thickness of the entire metal foil is preferably in this range, and the thickness of the ultrathin metal foil may be, for example, in the range of 0.1 μm to 10 μm.
[0032] The arithmetic mean roughness (Ra) of the surface of the metal foil that is bonded to the resin composition layer is preferably 100 nm or more, preferably 200 nm or more, more preferably 300 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the resin composition layer. The upper limit is not particularly limited, but is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The arithmetic mean roughness (Ra) is a value measured in accordance with ISO 25178, and can be measured using a non-contact surface roughness meter. An example of a non-contact surface roughness meter is "WYKO NT3300" manufactured by B-CO Instruments.
[0033] The metal foil may be a commercially available product. Examples of commercially available metal foils include "Microsyn MT18Ex" manufactured by Mitsui Mining & Smelting Co., Ltd., "HA-V2", "Microsyn MT18FL", "3EC-III", "3EC-M3-VLP", "3EC-M2S-VLP" manufactured by JX Metals Co., Ltd., "JDLC", "JTCSLC", "HA-V2", "HA", "HG" manufactured by JX Metals Mining Co., Ltd., and "CF-TX4-SV", "V9", "HD", "FLEQ HD", "FUTF", "RCF-T4X", "RCF-T5B" manufactured by Fukuda Metal Foil & Powder Co., Ltd.
[0034] <Resin composition layer> The resin sheet with the metal foil has a resin composition layer. The resin composition layer has a function of being thermally cured.
[0035] The component contained in the resin composition layer is preferably one whose cured product has sufficient hardness, a low linear thermal expansion coefficient, and insulating properties. An example of the component contained in such a resin composition layer is (A) an inorganic filler. In addition, the resin composition layer may contain (B) an epoxy resin, (C) a curing agent, (D) a curing accelerator, (E) a thermoplastic resin, (F) an organic filler, and (G) other additives as necessary.
[0036] -(A) Inorganic filler- The resin composition layer may contain an inorganic filler as component (A). By using a resin composition layer containing component (A), a cured product having a low linear thermal expansion coefficient can be obtained.
[0037] The (A) inorganic filler is contained in the resin composition layer in the form of particles. An inorganic compound is used as the material of the (A) inorganic filler. Examples of the material of the (A) inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (A) inorganic filler may be used alone or in combination of two or more kinds in any ratio.
[0038] Examples of commercially available inorganic fillers (A) include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellfiers" and "MGH-005" manufactured by Pacific Cement Corporation; and "Sferique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.
[0039] The average particle size of the (A) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.5 μm or less. The lower limit of the average particle size of the (A) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (A) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0040] The specific surface area of the (A) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of the inorganic filler (A) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2The specific surface area of the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0041] (A) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane, an organosilazane compound, and a titanate coupling agent. The surface treatment agent may be used alone or in any combination of two or more.
[0042] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0043] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.
[0044] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition layer or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0045] (A) The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.
[0046] From the viewpoint of obtaining a cured product with a low linear thermal expansion coefficient, the content of the (A) inorganic filler is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer. The upper limit is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less.
[0047] In the present invention, the content of each component in the resin composition layer is the value when the non-volatile components in the resin composition layer are 100 mass %, unless otherwise specified, and the non-volatile components mean all non-volatile components in the resin composition layer excluding the solvent.
[0048] -(B) Epoxy resin- The resin composition layer may contain an epoxy resin (B) in combination with the component (A). The epoxy resin (B) may be used alone or in combination of two or more kinds.
[0049] (B) Epoxy resins include, for example, bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl esters, and the like. Examples of epoxy resins that can be used include alicyclic epoxy resins such as cyclohexane-type epoxy resins, cresol novolac-type epoxy resins, biphenyl-type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, bicyclohexyl-type epoxy resins, and the like; heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane-type epoxy resins, cyclohexane dimethanol-type epoxy resins, naphthylene ether-type epoxy resins, trimethylol-type epoxy resins, tetraphenylethane-type epoxy resins, and phenolphthalimidine-type epoxy resins.
[0050] The resin composition layer preferably contains, as the component (B), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the epoxy resin (B) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0051] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as “liquid epoxy resins”) and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as “solid epoxy resins”). The resin composition layer may contain only a liquid epoxy resin or only a solid epoxy resin as component (B), and preferably contains a combination of a liquid epoxy resin and a solid epoxy resin.
[0052] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0053] As the liquid epoxy resin, preferred are alicyclic epoxy resins such as bicyclohexyl-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol AF-type epoxy resins, naphthalene-type epoxy resins, glycidyl ester-type epoxy resins, glycidyl amine-type epoxy resins, phenol novolac-type epoxy resins, cyclohexane-type epoxy resins, cyclohexane dimethanol-type epoxy resins, glycidyl amine-type epoxy resins, and epoxy resins having a butadiene structure, glycidyl cyclohexane-type epoxy resins, and phenolphthalimidine-type epoxy resins, with bisphenol A-type epoxy resins and alicyclic epoxy resins being more preferred, and bicyclohexyl-type epoxy resins being even more preferred.
[0054] Specific examples of liquid epoxy resins as component (B) include "Celloxide 8010" (bicyclohexyl type epoxy resin) manufactured by Daicel Corporation; "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resin) manufactured by DIC Corporation; "828US", "jER828EL" (bisphenol A type epoxy resin), "jER807" (bisphenol F type epoxy resin), and "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "JER-630" and "JER-630LSD" manufactured by Mitsubishi Chemical Corporation, and "ED-523T" (glycilol type epoxy resin (ADEKA glycilol) manufactured by ADEKA Corporation). Examples of such epoxy resins include "EP-3980S" (glycidylamine type epoxy resin), "EP-4088S" (dicyclopentadiene type epoxy resin), "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation, "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) and "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation, and "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical Co., Ltd. These may be used alone or in combination of two or more types.
[0055] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups in one molecule is preferable, a solid epoxy resin having three or more epoxy groups in one molecule is more preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is even more preferable.
[0056] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and biphenyl type epoxy resin, naphthalene type epoxy resin, and bixylenol type epoxy resin are more preferred.
[0057] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "NC3000L" manufactured by Nippon Kayaku Co., Ltd. Examples of epoxy resins include "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL6121" (biphenyl type epoxy resin), "YX4000H", "YX4000HK" (bixylenol type epoxy resin), and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; and "WHR-991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more.
[0058] As the (B) component, from the viewpoint of obtaining the effects of the present invention remarkably, it is preferable to use a combination of a liquid epoxy resin and a solid epoxy resin. In this case, the ratio by mass between them (liquid epoxy resin:solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:0.15 to 1:10, and particularly preferably 1:0.2 to 1:5. When the ratio by mass between the liquid epoxy resin and the solid epoxy resin is within the above range, the desired effects of the present invention can be obtained remarkably.
[0059] The epoxy equivalent of the (B) component is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, a cured product having sufficient crosslink density of the cured product of the resin composition layer can be obtained. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0060] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the component (B) is preferably 100 to 5000, more preferably 150 to 3000, and further preferably 200 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0061] The content of the (B) component is preferably 2% by mass or more, more preferably 6% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability. The upper limit of the epoxy resin content is preferably 35% by mass or less, more preferably 25% by mass or less, and particularly preferably 20% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.
[0062] The content of the liquid epoxy resin as component (B) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining the effects of the present invention prominently. The upper limit of the content of the liquid epoxy resin is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 8% by mass or less, from the viewpoint of obtaining the effects of the present invention prominently.
[0063] The content of the solid epoxy resin as component (B) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of significantly obtaining the effects of the present invention. The upper limit of the content of the solid epoxy resin is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 12% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.
[0064] -(C) Hardener- The resin composition layer may contain a (C) curing agent in combination with the (A) component. The (C) component does not include those corresponding to the (B) component. As the (C) curing agent, a compound having a function of reacting with the (B) component to cure the resin composition layer can be used, and examples thereof include carbodiimide-based curing agents, active ester-based curing agents, phenol-based curing agents, naphthol-based curing agents, benzoxazine-based curing agents, and cyanate ester-based curing agents. Among them, from the viewpoint of improving the insulation reliability, it is preferable that the (C) curing agent contains at least one of phenol-based curing agents, naphthol-based curing agents, active ester-based curing agents, and cyanate ester-based curing agents. The (C) curing agent may be used alone or in combination of two or more.
[0065] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable.
[0066] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", "EXB-9500", and "KA-1163" manufactured by DIC Corporation.
[0067] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0068] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0069] The carbodiimide curing agent is a compound having one or more carbodiimide groups (-N=C=N-) in one molecule, and the carbodiimide curing agent is preferably a compound having two or more carbodiimide groups in one molecule.
[0070] Specific examples of the carbodiimide-based curing agent include commercially available carbodiimide-based curing agents such as Carbodilite V-03 (carbodiimide group equivalent: 216, V-05 (carbodiimide group equivalent: 262), V-07 (carbodiimide group equivalent: 200), V-09 (carbodiimide group equivalent: 200), and Stavaxol P (carbodiimide group equivalent: 302), all manufactured by Nisshinbo Chemical Co., Ltd.
[0071] The active ester curing agent is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0072] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing an acetylated product of phenol novolac, and active ester compounds containing a benzoylated product of phenol novolac are preferred, and among these, active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.
[0073] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "HPC-8000L-65TM" (manufactured by DIC Corporation); active ester compounds containing a naphthalene structure, such as "EXB-9416-70BK", "EXB-8100L-65T", "EXB-8150-65T", "EXB-8150L-65T", "HPC-8150-60T", "HPC-8150-62T", and "HP-B-8151-62T" (manufactured by DIC Corporation); and phenol novolac. Examples of the active ester compound containing an acetylated product of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester compound containing a benzoylated product of phenol novolac includes "YLH1026" (manufactured by Mitsubishi Chemical Corporation), an active ester curing agent which is an acetylated product of phenol novolac includes "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester curing agent which is a benzoylated product of phenol novolac includes "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group includes "PC1300-02-65MA" (manufactured by Air Water Corporation).
[0074] The ratio of the amount of the epoxy resin (B) to the component (C) is preferably 1:0.01 to 1:5, more preferably 1:0.3 to 1:3, and even more preferably 1:0.5 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin (B)] to [total number of active groups in the component (C)]. Here, the "number of epoxy groups in the epoxy resin" refers to the total value of all values obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition layer by the epoxy equivalent. In addition, the "number of active groups in the component (C)" refers to the total value of all values obtained by dividing the mass of the non-volatile components of the component (C) present in the resin composition layer by the active group equivalent. By setting the ratio of the amount of the epoxy resin to the component (C) within this range, the effects of the present invention can be significantly obtained.
[0075] From the viewpoint of obtaining the desired effect of the present invention remarkably, the content of the (C) component is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer. The upper limit is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.
[0076] -(D) Curing accelerator- The resin composition layer may contain a curing accelerator (D) as the component (D). The curing accelerator (D) as the component (D) does not include those corresponding to the above-mentioned components (B) to (C). The curing accelerator (D) functions as a curing catalyst that accelerates the curing of the epoxy resin in the component (B).
[0077] As the (D) curing accelerator, a compound that accelerates the curing of the epoxy resin can be used. Examples of such (D) curing accelerators include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. As the (D) curing accelerator, one type may be used alone, or two or more types may be used in combination.
[0078] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.
[0079] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].
[0080] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.
[0081] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0082] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0083] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0084] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (D) curing accelerator is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, and is preferably 1.5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less.
[0085] -(E) Thermoplastic resin- The resin composition layer may contain a thermoplastic resin (E). The thermoplastic resin (E) as the component (E) does not include those corresponding to the above-mentioned components (B) to (D).
[0086] Examples of the (E) thermoplastic resin include phenoxy resin, polyimide resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. The (E) thermoplastic resin may be used alone or in combination of two or more kinds.
[0087] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.
[0088] Specific examples of polyimide resins include "PIAD100H" manufactured by Arakawa Chemical Industries, Ltd., "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0089] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0090] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0091] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0092] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0093] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0094] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0095] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.
[0096] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.
[0097] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.
[0098] The weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably greater than 5,000, more preferably 8,000 or more, even more preferably 10,000 or more, and particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, and particularly preferably 50,000 or less.
[0099] In order to obtain the effects of the present invention more significantly, the content of the (E) thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and particularly preferably 0.3% by mass or more, when the non-volatile components in the resin composition layer are taken as 100% by mass, and is preferably 5% by mass or less, more preferably 3% by mass or less, and particularly preferably 2% by mass or less.
[0100] -(F)Organic filler- The resin composition layer may contain an organic filler (F) as the component (F). The organic filler (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). As the organic filler, any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, and examples of the organic filler include rubber particles, polyamide fine particles, silicone particles, etc.
[0101] As the rubber particles, commercially available products may be used, for example, "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.
[0102] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (F) organic filler is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, and is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1.5% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.
[0103] -(G) Other additives- The resin composition layer may contain (G) other additives as an optional non-volatile component. (G) Optional additives include, for example, organic fillers; polymerization initiators; organometallic compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters; hindered phenol-based acids. fluorescent brightening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiation assistants such as tertiary amines; and photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, and thioxanthones. The optional additives (G) may be used alone or in combination of two or more kinds.
[0104] The resin composition layer may contain a solvent as a volatile component. The amount of the solvent such as an organic solvent is preferably small from the viewpoint of adjusting the elastic modulus of the resin composition layer. The amount of the solvent in the resin composition layer (residual solvent amount) is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2.5% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less. There is no particular restriction on the lower limit, but it may be 0.0001% by mass or more. The residual solvent amount can be measured by the method described in the examples below.
[0105] Examples of the solvent include ketones such as methyl ethyl ketone (MEK) and cyclohexanone, aromatic hydrocarbons such as xylene and tetramethylbenzene, glycol ethers such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether, esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate, and ethyl diglycol acetate, aliphatic hydrocarbons such as octane and decane, and petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These may be used alone or in combination of two or more.
[0106] From the viewpoint of obtaining the effects of the present invention more prominently, the resin composition layer preferably contains a liquid resin. The liquid resin refers to a resin among the components (B) to (G) that is liquid at a temperature of 20° C. The liquid resin is preferably a liquid epoxy resin.
[0107] The content of the liquid resin is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition layer, from the viewpoint of obtaining the effects of the present invention remarkably. The upper limit of the content of the liquid resin is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 8% by mass or less, from the viewpoint of obtaining the effects of the present invention remarkably.
[0108] <Protective film> The resin sheet with the metal foil includes a protective film. By laminating the protective film on the resin sheet with the metal foil, it is possible to prevent the adhesion of dirt and the like and scratches on the surface of the resin composition layer.
[0109] Examples of the protective film include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0110] When a film made of a plastic material is used as the protective film, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0111] When a metal foil is used as the protective film, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0112] The surface of the protective film that is to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0113] In addition, as the protective film, a protective film with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the protective film with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The protective film with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60", "Lumirror R80", and "Lumirror" manufactured by Toray Industries, "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0114] The thickness of the protective film is as described above. When the protective film has a multi-layer structure such as a protective film with a release layer, the total thickness of the protective film is preferably in the above range.
[0115] <Method for producing resin sheet with metal foil, and method for producing roll-shaped resin sheet with metal foil> The method for producing a resin sheet with metal foil is, for example, to prepare a resin varnish by dissolving the components contained in the resin composition layer in a solvent, and then to apply the resin varnish to a protective film using a die coater or the like, and then to dry the resin composition layer on the protective film. Then, a metal foil is laminated to the surface of the resin composition layer using a roll laminator or the like, thereby producing a resin sheet with metal foil. The above-mentioned solvents can be used.
[0116] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0117] The resin sheet with metal foil may be produced by applying a resin varnish onto a metal foil and then drying the applied resin varnish to form a resin composition layer.
[0118] The resin sheet with the metal foil can be wound into a roll to produce a roll-shaped resin sheet with the metal foil. The resin sheet with the metal foil is preferably wound with the metal foil on the outside and the protective film on the inside.
[0119] From the viewpoint of obtaining the effects of the present invention significantly, the winding diameter of the rolled resin sheet with metal foil is preferably 5 cm or more, more preferably 6 cm or more, and even more preferably 7 cm or more, and is preferably 20 cm or less, more preferably 16 cm or less, and even more preferably 12 cm or less. Even if the resin sheet with metal foil is wound into a roll so that the winding diameter is within this range, the resin sheet with metal foil of the present invention satisfies formulas (1) and (2), and therefore an increase in the stress applied to each layer can be suppressed. The winding diameter of the rolled resin sheet with metal foil refers to the diameter of the winding core.
[0120] <Physical properties of resin sheets with metal foil> The resin sheet with metal foil of the present invention exhibits the property that the elastic modulus and thickness of each layer satisfy formula (1) and formula (2), and thus can be produced into a roll of the resin sheet with metal foil. Therefore, the resin sheet with metal foil of the present invention has excellent roll formability. When the resin sheet with metal foil was cut into a size of 40 cm x 40 cm and wound around a cylinder with a diameter of 6 cm at 25°C, a winding tension of 0.2 kgf / cm, and a winding speed of 5 m / min, no folds or cracks occurred in the resin sheet with metal foil. The roll formability can be evaluated by the method described in the examples below.
[0121] The resin sheet with metal foil of the present invention usually exhibits the characteristic that the linear thermal expansion coefficient (CTE) of the cured product of the resin composition layer is low. Thus, the cured product provides an insulating layer with a low linear thermal expansion coefficient. The linear thermal expansion coefficient is preferably 40 ppm / °C or less, more preferably 35 ppm / °C or less, and more preferably 30 ppm / °C or less. The lower limit is not particularly limited, but may be 1 ppm / °C or more. The linear thermal expansion coefficient can be measured according to the method described in the examples below.
[0122] The resin sheet with metal foil of the present invention usually exhibits the characteristic that the glass transition temperature (Tg) of the cured product of the resin composition layer is high. Therefore, an insulating layer with a high glass transition temperature is obtained. The glass transition temperature of the cured product of the resin composition layer is preferably 140°C or higher, more preferably 145°C or higher, and further preferably 150°C or higher. The upper limit is not particularly limited, but may be, for example, 300°C or lower. The glass transition temperature (Tg) can be measured by the method described in the examples below.
[0123] The resin sheet with metal foil of the present invention usually exhibits the characteristic that the breaking strength of the cured resin composition layer is high. Therefore, an insulating layer with high breaking strength is obtained. The breaking strength is preferably 50 MPa or more, more preferably 80 MPa or more, and even more preferably 100 MPa or more. The upper limit is not particularly limited, but may be, for example, 300 MPa or less. The breaking strength can be measured by the method described in the examples below.
[0124] The resin sheet with metal foil of the present invention usually exhibits the property that the metal foil does not wrinkle even when the resin sheet with metal foil from which the protective film has been peeled off is bonded to an inner layer substrate. Therefore, the resin sheet with metal foil of the present invention has excellent lamination properties. For example, the protective film of the resin sheet with metal foil is peeled off, and the resin composition layer is laminated using a vacuum laminator so that it contacts the undercoated inner layer substrate. The metal foil on the laminated undercoated inner layer substrate usually does not wrinkle. The lamination properties can be evaluated by the method described in the Examples below.
[0125] The resin sheet with metal foil of the present invention usually exhibits the property that a part of the resin composition layer is suppressed from peeling off together with the protective film. Therefore, the resin sheet with metal foil of the present invention has excellent peelability. For example, when the surface of the resin composition layer of the resin sheet with metal foil from which the protective film has been peeled off is visually observed, a part of the resin composition layer is not peeled off together with the protective film, and the metal foil is not exposed. The peelability can be evaluated by the method described in the examples below.
[0126] The resin sheet with metal foil of the present invention has excellent roll formability, and can provide an insulating layer with high breaking strength and glass transition temperature and low linear thermal expansion coefficient. Therefore, the resin sheet with metal foil of the present invention can be suitably used as a resin sheet for forming both an insulating layer and a conductor layer (for forming an insulating layer and a conductor layer) in the manufacture of a circuit board, can be suitably used as a resin sheet for forming both an insulating layer and a conductor layer by using a vacuum hot press process in the manufacture of a circuit board (for forming an insulating layer and a conductor layer by using a vacuum hot press process), can be suitably used as a resin sheet for forming both an insulating layer and a conductor layer (for forming an insulating layer and a conductor layer) in the manufacture of a printed wiring board, and can be suitably used as a resin sheet for forming both an insulating layer and a conductor layer by using a vacuum hot press process in the manufacture of a printed wiring board (for forming an insulating layer and a conductor layer by using a vacuum hot press process).
[0127] [Circuit board] The circuit board of the present invention can be produced by using the resin sheet with a metal foil of the present invention. That is, it is possible to provide a circuit board including an insulating layer made of a cured product of the resin composition layer of the resin sheet with a metal foil of the present invention, and a conductor layer formed from a metal foil.
[0128] One embodiment of the circuit board is a printed wiring board, which includes an insulating layer made of a cured product of the resin composition layer of the resin sheet with metal foil of the present invention, and a conductor layer formed from metal foil.
[0129] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet with a metal foil or a roll-shaped resin sheet with a metal foil, by a method including the following steps (I) and (II). (I) A step of laminating a resin composition layer of a resin sheet with a metal foil on an inner layer substrate by vacuum hot pressing. (II) A step of thermally curing the resin composition layer to form an insulating layer
[0130] The "inner layer substrate" used in step (I) is a member that becomes the substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0131] The inner layer substrate and the resin sheet with the metal foil are laminated by peeling off the protective film and then performing a vacuum hot press treatment so that the resin composition layer of the resin sheet with the metal foil is bonded to the inner layer substrate.
[0132] First, the protective film of the resin sheet with the metal foil is peeled off, and the inner layer substrate and the resin sheet with the metal foil from which the protective film has been peeled off are set in a vacuum hot press device so that the resin composition layer of the resin sheet with the metal foil is bonded to the inner layer substrate. Next, a vacuum hot press process is performed to heat and press the inner layer substrate and the resin composition layer under reduced pressure conditions.
[0133] The resin sheet with the metal foil from which the inner layer substrate and protective film have been peeled off may be set in a vacuum hot press device via cushion paper, a metal plate such as a stainless steel plate (SUS plate), a release film, or the like.
[0134] The vacuum hot press treatment can be carried out using a conventionally known vacuum hot press apparatus that presses the resin sheet with the metal foil from which the inner layer substrate and the protective film have been peeled off from both sides with a heated metal plate such as a SUS plate. An example of a commercially available vacuum hot press apparatus is "VH1-1603" manufactured by Kitagawa Seiki Co., Ltd.
[0135] The vacuum hot pressing treatment may be carried out only once, or may be carried out repeatedly two or more times. When it is carried out repeatedly two or more times, the pressure, heating temperature, pressing time, etc. may be the same or different.
[0136] In the vacuum hot press treatment, the pressure (pressing force) is preferably 5 kgf / cm 2 More preferably, 10kgf / cm 2 More preferably, 15 kgf / cm 2 More than 50kgf / cm 2 Less than or equal to 35kgf / cm 2 Less than 25kgf / cm, more preferably 25kgf / cm 2 The following is the result.
[0137] In the vacuum hot press process, the atmospheric pressure, i.e., the pressure (degree of vacuum) during decompression in the chamber in which the laminated structure to be processed is stored, is preferably 3×10 -2 MPa or less, more preferably 1×10 -2 MPa or less. There is no particular lower limit, but it is 1×10 -10 MPa or more.
[0138] In the vacuum hot press treatment, the heating temperature varies depending on the composition of the resin composition layer, but is preferably 80° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher. The upper limit of the heating temperature is not particularly limited, but may usually be 300° C. or lower. The resin composition layer may be thermally cured by heating in the vacuum hot press treatment to form an insulating layer.
[0139] In the vacuum hot press treatment, the pressing time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more. The upper limit is not particularly limited, but is preferably 300 minutes or less, more preferably 200 minutes or less, and even more preferably 150 minutes or less.
[0140] The resin sheet with the metal foil from which the protective film has been peeled off is laminated on the inner layer substrate by vacuum pressing, and then in step (II), the resin composition layer is thermally cured to form an insulating layer. For example, when performing pressing by vacuum hot pressing, the resin composition layer is thermally cured by using heat generated during pressing to form an insulating layer.
[0141] The conditions for thermally curing the resin composition layer are not particularly limited, and conditions that are usually employed when forming an insulating layer for a printed wiring board may be used.
[0142] For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition layer, but the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0143] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. or more and less than 120° C. (preferably 60° C. or more and 115° C. or less, more preferably 70° C. or more and 110° C. or less) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).
[0144] The resin sheet with metal foil used in the present invention contains metal foil, and therefore may include, as step (III), a step of forming a conductor layer (circuit) by a subtractive method or a modified semi-additive method.
[0145] In the step (III), the metal foil in the resin sheet with the metal foil can be used to form a conductor layer by a subtractive method or a modified semi-additive method.
[0146] In the subtractive method, unnecessary parts (non-circuit forming parts) of the metal foil are selectively removed by etching or the like to form a circuit. The circuit formation by the subtractive method may be carried out according to a known procedure. For example, the circuit formation by the subtractive method can be carried out by a method including: i) providing an etching resist on the surface of the metal foil (i.e., the surface opposite to the surface bonded to the resin composition layer); ii) exposing and developing the etching resist to form a wiring pattern; iii) etching and removing the exposed metal foil parts; and iv) removing the etching resist.
[0147] In the modified semi-additive method, the non-circuit forming portion of the metal foil is protected by a plating resist, and a metal such as copper is thickly applied to the circuit forming portion by electrolytic plating, and then the plating resist is removed, and the metal foil other than the circuit forming portion is removed by etching to form a circuit. The circuit formation by the modified semi-additive method may be carried out according to a known procedure. For example, the circuit formation by the modified semi-additive method can be carried out by a method including: i) providing a plating resist on the surface of the metal foil (i.e., the surface opposite to the surface bonded to the resin composition layer), ii) exposing and developing the plating resist to form a wiring pattern, iii) electroplating through the plating resist, iv) removing the plating resist, and v) etching and removing the metal foil other than the circuit forming portion. In addition, when the metal foil is thick, the entire surface of the metal foil may be thinned by etching or the like before the above i) so that the metal foil has a desired thickness (usually 5 μm or less, 4 μm or less, or 3 μm or less).
[0148] In manufacturing a printed wiring board, a step (IV) of drilling holes and a step (V) of roughening the insulating layer may be further carried out. These steps (IV) to (V) may be carried out according to various methods known to those skilled in the art and used in manufacturing printed wiring boards. Furthermore, if necessary, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a multilayer wiring board.
[0149] [Semiconductor Devices] The semiconductor device of the present invention includes the circuit board or printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured using the circuit board or printed wiring board of the present invention.
[0150] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft).
[0151] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. The "conductive portion" refers to a portion of a printed wiring board that transmits an electric signal, and the portion may be either on the surface or embedded. The semiconductor chip is not particularly limited as long as it is an electric circuit element made of semiconductor material.
[0152] The method of mounting a semiconductor chip when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip functions effectively, but specific examples include a wire bonding mounting method, a flip chip mounting method, a bumpless buildup layer (BBUL) mounting method, an anisotropic conductive film (ACF) mounting method, a non-conductive film (NCF) mounting method, etc. Here, the "bumpless buildup layer (BBUL) mounting method" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess in a printed wiring board and the semiconductor chip is connected to the wiring on the printed wiring board." EXAMPLES
[0153] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0154] <Formulation Example 1> Preparation of Resin Varnish 1 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight: about 269 g / eq.), 15 parts of bisphenol A type epoxy resin ("828EL" manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent weight: about 180 g / eq.), 5 parts of bicyclohexyl type epoxy resin ("Celloxide 8010" manufactured by Daicel Co., Ltd., epoxy equivalent weight: about 97 g / eq.), and 40 parts of methyl ethyl ketone (MEK) were added and dissolved by heating with stirring. This was cooled to room temperature to prepare an epoxy resin dissolved composition. To this epoxy resin solution, 10 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%), 50 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), and 10 parts of a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573" were added. Resin varnish 1 was prepared by mixing 180 parts of spherical silica ("SO-C2" manufactured by Admatechs, average particle size 0.5 μm) surface-treated with 1,000 sucrose (NaCl), 1 ...
[0155] <Formulation Example 2> Preparation of Resin Varnish 2 In Mixture Example 1, 1) The amount of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight approximately 269g / eq.) was changed from 20 parts to 10 parts. 2) In addition, 10 parts of bixylenol type epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation) was used. Resin varnish 2 was prepared in the same manner as in Formulation Example 1 except for the above.
[0156] <Formulation Example 3> Preparation of Resin Varnish 3 In Mixture Example 1, 1) The amount of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight approximately 269g / eq.) was changed from 20 parts to 10 parts. 2) In addition, 10 parts of naphthalene type epoxy resin ("HP4032SS" manufactured by DIC Corporation) was used. Resin varnish 3 was prepared in the same manner as in Formulation Example 1 except for the above.
[0157] <Formulation Example 4> Preparation of Resin Varnish 4 In Mixture Example 1, 1) The amount of bisphenol A epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent approximately 180g / eq.) was changed from 15 parts to 20 parts. 2) Bicyclohexyl type epoxy resin (Daicel Corporation's "Celloxide 8010", epoxy equivalent: approximately 97 g / eq.) was not used. Resin varnish 4 was prepared in the same manner as in Formulation Example 1 except for the above.
[0158] <Formulation Example 5> Preparation of Resin Varnish 5 In Mixture Example 1, 1) The amount of triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of approximately 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) was changed from 10 parts to 75 parts. 2) No active ester compound (DIC Corporation's "HPC-8000-65T," active ester group equivalent of approximately 223 g / eq., toluene solution with non-volatile content of 65%) was used. Resin varnish 5 was prepared in the same manner as in Formulation Example 1 except for the above.
[0159] <Formulation Example 6> Preparation of Resin Varnish 6 In Mixture Example 1, Further, 17 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass) was used. Resin varnish 6 was prepared in the same manner as in Formulation Example 1 except for the above.
[0160] <Formulation Example 7> Preparation of Resin Varnish 7 In Mixture Example 1, Further, 25 parts of polyvinyl butyral resin ("KS-1" manufactured by Sekisui Chemical Co., Ltd., a toluene solution with a solid content of 20% by mass) was used. Resin varnish 7 was prepared in the same manner as in Formulation Example 1 except for the above.
[0161] <Formulation Example 8> Preparation of Resin Varnish 8 In Mixture Example 1, 17 parts of polyimide resin ("PIAD100H" manufactured by Arakawa Chemical Industries, Ltd., a mixed solution of cyclohexanone and methylcyclohexane with a non-volatile content of 30% by mass) was used. Resin varnish 8 was prepared in the same manner as in Formulation Example 1 except for the above points.
[0162] <Formulation Example 9> Preparation of Resin Varnish 9 In Mixture Example 1, Further, 10 parts of a carbodiimide resin ("V-03" manufactured by Nisshinbo Chemical Inc., active group equivalent weight approximately 216 g / eq., toluene solution with non-volatile content of 50% by mass) was used. Resin varnish 9 was prepared in the same manner as in Formulation Example 1 except for the above.
[0163] <Formulation Example 10> Preparation of Resin Varnish 10 In Mixture Example 1, Furthermore, 2 parts of an organic filler (rubber particles, "Staphyloid AC3816N" manufactured by Aica Kogyo Co., Ltd.) was used. Resin varnish 10 was prepared in the same manner as in Formulation Example 1 except for the above points.
[0164] <Formulation Example 11> Preparation of Resin Varnish 11 In Mixture Example 1, The amount of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 180 parts to 220 parts. Resin varnish 11 was prepared in the same manner as in Formulation Example 1 except for the above.
[0165] <Formulation Example 12> Preparation of Resin Varnish 12 In Mixture Example 1, 1) The amount of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent approximately 180g / eq.) was changed from 15 parts to 10 parts. 2) The amount of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 180 parts to 100 parts. Resin varnish 12 was prepared in the same manner as in Formulation Example 1 except for the above points.
[0166] <Formulation Example 13> Preparation of Resin Varnish 13 In Mixture Example 1, 1) The amount of bisphenol A epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent approximately 180g / eq.) was changed from 15 parts to 20 parts. 2) The amount of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 180 parts to 370 parts. Resin varnish 13 was prepared in the same manner as in Formulation Example 1 except for the above points.
[0167] <Formulation Example 14> Preparation of Resin Varnish 14 In Mixture Example 1, 1) The amount of bisphenol A epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent weight approximately 180g / eq.) was changed from 15 parts to 5 parts. 2) The amount of bicyclohexyl epoxy resin (Daicel's "Celloxide 8010", epoxy equivalent: approx. 97 g / eq.) was changed from 5 parts to 2 parts. 3) The amount of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 180 parts to 40 parts. Resin varnish 14 was prepared in the same manner as in Formulation Example 1 except for the above points.
[0168] <Formulation Example 15> Preparation of Resin Varnish 15 In Mixture Example 1, 1) The amount of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent approximately 180g / eq.) was changed from 15 parts to 25 parts. 2) The amount of bicyclohexyl type epoxy resin (Daicel Corporation's "Celloxide 8010", epoxy equivalent approximately 97 g / eq.) was changed from 5 parts to 10 parts. 3) The amount of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 269 g / eq.) was changed from 20 parts to 5 parts. Resin varnish 15 was prepared in the same manner as in Formulation Example 1 except for the above.
[0169] <Formulation Example 16> Preparation of Resin Varnish 16 In Mixture Example 1, 1) The amount of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent weight approximately 180g / eq.) was changed from 15 parts to 4 parts. 2) The amount of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: approximately 269 g / eq.) was changed from 20 parts to 30 parts. Resin varnish 16 was prepared in the same manner as in Formulation Example 1 except for the above.
[0170] <Example 1> The resin varnish 1 obtained in Formulation Example 1 was applied to the release surface of a release-treated polyethylene terephthalate film (Toray Industries, Inc., "Lumirror R80," thickness 38 μm) as the protective film 1 using a die coater so that the thickness of the resin composition layer was 40 μm, and dried at 80 to 120° C. (average 100° C.) for 6 minutes so that the residual solvent amount (a method for measuring the residual solvent amount will be described later) was 1.8%, to obtain a sheet with a protective film. Next, the metal foil 1 was laminated on the surface of the resin composition layer using a roll laminator (Taisei Laminator Co., Ltd., "FIRST LAMINATOR The sheets were laminated together using a roll pressure of 0.25 MPa, a feed rate of 0.3 m / min, and a roll temperature of 90° C., to obtain a resin sheet 1 with a metal foil.
[0171] <Example 2> In Example 1, Resin Varnish 1 was changed to Resin Varnish 2. A resin sheet 2 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0172] <Example 3> In Example 1, Resin Varnish 1 was changed to Resin Varnish 3. A resin sheet 3 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0173] <Example 4> In Example 1, Resin Varnish 1 was changed to Resin Varnish 4. A resin sheet 4 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0174] <Example 5> In Example 1, Resin Varnish 1 was changed to Resin Varnish 5. A resin sheet 5 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0175] <Example 6> In Example 1, Resin Varnish 1 was changed to Resin Varnish 6. A resin sheet 6 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0176] <Example 7> In Example 1, Resin Varnish 1 was changed to Resin Varnish 7. Resin sheet 7 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0177] <Example 8> In Example 1, Resin Varnish 1 was changed to Resin Varnish 8. A resin sheet 8 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0178] <Example 9> In Example 1, Resin Varnish 1 was changed to Resin Varnish 9. A resin sheet 9 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0179] <Example 10> In Example 1, the resin varnish 1 was changed to the resin varnish 10. A resin sheet 10 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0180] <Example 11> In Example 1, Resin Varnish 1 was changed to Resin Varnish 11. A resin sheet 11 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0181] <Example 12> In Example 1, Resin Varnish 1 was changed to Resin Varnish 12. A resin sheet 12 with a metal foil was obtained in the same manner as in Example 1 except for the above points.
[0182] <Example 13> The thickness of the resin composition layer was changed from 40 μm to 10 μm in Example 1. A resin sheet 13 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0183] <Example 14> In Example 1, the release-treated polyethylene terephthalate film ("Lumirror" manufactured by Toray Industries, Inc., thickness 38 μm) serving as protective film 1 was changed to a release-treated polyethylene terephthalate film ("Lumirror" manufactured by Toray Industries, Inc., thickness 12 μm) serving as protective film 2. A resin sheet 14 with a metal foil was obtained in the same manner as in Example 1 except for the above points.
[0184] <Example 15> In Example 1, the carrier-attached copper foil (Mitsui Mining & Smelting Co., Ltd.'s "Microthin MT18Ex", 3 μm-thick ultra-thin copper foil / 18 μm-thick carrier copper foil) comprising the carrier copper foil and ultra-thin copper foil as the metal foil 1 was changed to a copper foil (JX Nippon Mining & Smelting Co., Ltd.'s "HA-V2", 6 μm-thick) as the metal foil 2. A resin sheet 15 with a metal foil was obtained in the same manner as in Example 1 except for the above points.
[0185] <Comparative Example 1> In Example 1, Resin Varnish 1 was changed to Resin Varnish 13. A resin sheet 16 with a metal foil was obtained in the same manner as in Example 1 except for the above points.
[0186] <Comparative Example 2> In Example 1, the resin varnish 1 was changed to the resin varnish 14. A resin sheet 17 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0187] <Comparative Example 3> In Example 1, Resin Varnish 1 was changed to Resin Varnish 15. A resin sheet 18 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0188] <Comparative Example 4> In Example 1, the resin varnish 1 was changed to the resin varnish 16. A resin sheet 19 with a metal foil was obtained in the same manner as in Example 1 except for the above-mentioned points.
[0189] <Comparative Example 5> In Example 1, the release-treated polyethylene terephthalate film (Toray Industries, Inc., "Lumirror R80," thickness 38 μm) serving as protective film 1 was changed to a release-treated polyethylene terephthalate film (Toray Industries, Inc., "Lumirror," thickness 2 μm) serving as protective film 3. A resin sheet 20 with a metal foil was obtained in the same manner as in Example 1, except for the above points.
[0190] <Comparative Example 6> In Example 1, the release-treated polyethylene terephthalate film (Toray Industries, Inc., "Lumirror R80," thickness 38 μm) used as protective film 1 was changed to a release-treated polyethylene terephthalate film (Toray Industries, Inc., "Lumirror," thickness 250 μm) used as protective film 4. A resin sheet 21 with a metal foil was obtained in the same manner as in Example 1, except for the above points.
[0191] <Comparative Example 7> In Example 1, the 18 μm thick carrier copper foil of the resin sheet 1 with the metal foil was peeled off to make the thickness of the metal foil 3 μm. This metal foil is referred to as metal foil 3. A resin sheet 22 with the metal foil was obtained in the same manner as in Example 1 except for the above points.
[0192] <Comparative Example 8> In Example 1, the carrier-attached copper foil (Mitsui Mining & Smelting Co., Ltd.'s "Microthin MT18Ex", 3 μm-thick ultra-thin copper foil / 18 μm-thick carrier copper foil) comprising the carrier copper foil and ultra-thin copper foil as the metal foil 1 was changed to a copper foil (JX Nippon Mining & Smelting Co., Ltd.'s "HA-V2", 150 μm-thick) as the metal foil 4. A resin sheet 23 with a metal foil was obtained in the same manner as in Example 1 except for the above points.
[0193] <Thickness measurement> The thickness of each layer in the metal foil-attached resin sheets 1 to 23 was measured using a contact thickness meter (MCD-25MJ, manufactured by Mitutoyo Corporation). The thickness of the resin composition layer was measured using the contact thickness meter before bonding the metal foil.
[0194] <Measurement of elastic modulus of metal foil and protective film> The metal foil and the protective film were cut into dumbbell-shaped No. 1 test pieces to obtain test pieces. The test pieces were subjected to tensile strength measurement using a tensile tester "RTC-1250A" manufactured by Orientec Co., Ltd., and the elastic modulus was calculated (measurement temperature: 23°C). The measurement was performed in accordance with JIS K7127. The measurement was performed three times in the MD direction, and the average value was calculated (unit: GPa).
[0195] <Measurement of Elastic Modulus of Resin Composition Layer> Resin varnishes 1 to 16 obtained in Formulation Examples 1 to 16 were applied to the release surface of a support, a polyethylene terephthalate film with release treatment (Toray's "Lumirror R80, thickness 38 μm) so that the thickness of the resin composition layer was 40 μm, using a die coater, and dried at 80 to 120 ° C (average 100 ° C) so that the residual solvent amount was 2.0 mass %. After peeling off the support, four sheets of the same resin composition layer were stacked to obtain a laminate of resin composition layers with a thickness of 160 μm, and cut into a dumbbell shape No. 1 to obtain a test piece. The test piece was subjected to tensile strength measurement using a tensile tester "RTC-1250A" manufactured by Orientec Co., Ltd., and the elastic modulus was obtained. The measurement was performed in accordance with JIS K7127. The measurement was performed three times, and the average value was calculated (unit: GPa).
[0196] <Measurement of Residual Solvent Amount in Resin Composition Layer> 1) Mass measurement of protective film A sheet with a protective film before laminating the metal foil was prepared when manufacturing the resin sheets 1 to 23 with metal foil. Next, the protective film was cut into a size of 10 cm x 10 cm, and the weight was measured using an electronic balance. The measurement was performed on three samples, and the average value was taken as the mass of the protective film.
[0197] 2) Measurement of residual solvent amount Each sheet with protective film was cut into a size of 10 cm x 10 cm, and the initial mass was measured using an electronic balance. Next, the sheet with protective film was placed on a wire net, heated in an oven previously set at 130 ° C for 15 minutes, then transferred to a desiccator and left to stand for 30 minutes, and cooled to room temperature. Then, the dry mass of the sheet with protective film was measured using an electronic balance. The initial mass and dry mass were both measured for three samples, and the average value was used to calculate the amount of solvent (residual solvent amount) contained in the resin composition layer using the following formula. Residual solvent amount (mass%) = 100 × (initial mass of sheet with protective film - dry mass of sheet with protective film) / (initial mass of sheet with protective film - mass of protective film)
[0198] [Table 1]
[0199] [Table 2]
[0200] <Measurement of glass transition temperature, linear thermal expansion coefficient, and breaking strength> -Preparation of cured material for evaluation- The protective film of the metal foil-attached resin sheets 1 to 23 was peeled off, and a vacuum laminator was used to laminate the copper foil ("Microthin MT18Ex" manufactured by Mitsui Mining & Smelting Co., Ltd.) and the resin composition layer so as to be bonded to each other. The laminated resin sheet was pressed using a vacuum hot press machine (VH1-1603 manufactured by Kitagawa Seiki Co., Ltd.) at a vacuum degree of 1×10 -3 MPa or less, pressure condition is 20kgf / cm 2 The heating conditions were a first press at 100°C for 30 minutes, and a second press at 190°C for 120 minutes to thermally cure the resin composition layer and obtain a laminate. The laminate was immersed in an aqueous solution of iron (II) chloride (Tsurumi Soda Co., Ltd., Baume degree 40) and the metal foil and copper foil were removed to obtain a sheet-like cured product. The obtained sheet-like cured product is referred to as the "cured product for evaluation."
[0201] -Measurement of glass transition temperature and linear thermal expansion coefficient- The cured product for evaluation was cut into test pieces with a width of about 5 mm and a length of about 15 mm, and a thermomechanical analysis was performed by the tensile load method using a thermomechanical analyzer (Rigaku's "Thermo Plus TMA8310"). In detail, the test pieces were mounted on the thermomechanical analyzer, and then measured twice consecutively under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. In the second measurement, the glass transition temperature (Tg;°C) and the average coefficient of linear thermal expansion (CTE; ppm / °C) in the range from 25°C to 150°C were calculated.
[0202] -Measurement of breaking strength- The cured product for evaluation was cut into a dumbbell-shaped No. 1 test piece to obtain it. The test piece was subjected to tensile strength measurement using a tensile tester "RTC-1250A" manufactured by Orientec Co., Ltd., and the breaking strength of the cured product for evaluation was obtained. The measurement was performed in accordance with JIS K7127. This operation was performed three times, and the average value was calculated (unit: GPa).
[0203] <Evaluation of roll formability> The metal foil-attached resin sheets 1 to 23 were cut to 40 cm x 40 cm and wrapped around a cylinder with a diameter of 6 cm at 25°C, a winding tension of 0.2 kgf / cm, and a winding speed of 5 m / min. The metal foil-attached resin sheets 1 to 23 were visually observed to determine whether they had any folds or cracks, and evaluated according to the following criteria. ◯: No folds or cracks occurred in the resin sheet with the metal foil. ×: The resin sheet with the metal foil was bent or cracked.
[0204] <Evaluation of peelability of protective film> The protective film was peeled off from the metal foil-attached resin sheets 1 to 23. The surface of the resin composition layer of the metal foil-attached resin sheet from which the protective film was peeled off was visually observed and evaluated according to the following criteria. ◯: A part of the resin composition layer was not peeled off together with the protective film, and the metal foil was not exposed. ×: A part of the resin composition layer was peeled off together with the protective film, exposing the metal foil.
[0205] <Evaluation of lamination properties> The protective film was peeled off from the metal foil-attached resin sheets 1 to 23, and the resin composition layer was laminated to the substrate-treated inner layer substrate using a vacuum laminator so that the resin composition layer was in contact with the substrate-treated inner layer substrate to obtain a substrate for evaluation. The substrate for evaluation was visually judged and evaluated according to the following criteria. ◯: No wrinkles were observed in the metal foil on the evaluation substrate. ×: Wrinkles occurred in the metal foil on the evaluation substrate.
[0206] [Table 3]
[0207] [Table 4]
Claims
1. A resin sheet with a metal foil, comprising a metal foil, a resin composition layer, and a protective film laminated in this order, The resin composition layer contains a liquid resin, The content of the liquid resin is 5% by mass or more and 25% by mass or less, when the non-volatile components in the resin composition layer are taken as 100% by mass, The thickness of the resin composition layer is 5 μm or more and 60 μm or less, The elastic modulus B (GPa) of the resin composition layer before curing at 23°C is 1 GPa or more and 10 GPa or less, The thickness of the metal foil is a (μm), and the elastic modulus of the metal foil at 23° C. is A (GPa). The thickness of the resin composition layer is b (μm), and the elastic modulus of the resin composition layer before curing at 23° C. is B (GPa). When the thickness of the protective film is c (μm) and the elastic modulus of the protective film at 23° C. is C (GPa), A resin sheet with a metal foil, which satisfies both of the following formulas (1) and (2): 0.2≦(c×C) / (b×B)≦8 (1) 4≦(a×A) / (b×B)≦30 (2)
2. The resin sheet with a metal foil according to claim 1 , wherein the resin composition layer contains (A) an inorganic filler.
3. The resin sheet with a metal foil according to claim 2 , wherein the content of the component (A) is 55% by mass or more and 85% by mass or less, based on 100% by mass of non-volatile components in the resin composition layer.
4. The resin sheet with a metal foil according to claim 1 , wherein the resin composition layer comprises an epoxy resin (B).
5. 2. The resin sheet with a metal foil according to claim 1, wherein a / b is 0.1 or more and 2 or less, where a (μm) is the thickness of the metal foil and b (μm) is the thickness of the resin composition layer.
6. 2. The resin sheet with a metal foil according to claim 1, wherein c / b is 0.3 or more and 4 or less, where b (μm) is the thickness of the resin composition layer and c (μm) is the thickness of the protective film.
7. The resin sheet with a metal foil according to claim 1 , wherein the metal foil is a copper foil.
8. A roll-shaped resin sheet with a metal foil, which is obtained by winding up the resin sheet with a metal foil according to any one of claims 1 to 7 into a roll.
9. The roll-shaped resin sheet with a metal foil according to claim 8, having a winding diameter of 6 cm or more.
10. A circuit board comprising: an insulating layer formed from a cured product of a resin composition layer of the resin sheet with a metal foil according to any one of claims 1 to 7; and a conductor layer formed from the metal foil of the resin sheet with a metal foil according to any one of claims 1 to 7.
11. A semiconductor device comprising the circuit board according to claim 10.
Citation Information
Patent Citations
Heat-resistant film preservative method and heat-resistant film package
JP2004059084A
Flexible copper-clad laminate and its manufacturing method
JP2005280163A
Flexible copper clad laminated board and its manufacturing method
JP2009172996A
Antenna beam control device
JP2010161497A
Insulating resin film, production method of insulating resin film, preliminarily cured product, laminate, and multilayer substrate
JP2014062150A